Radicali

  • Materia: Radicali
  • Visto: 3030
  • Data: 18/10/2009
  • Di: Redazione StudentVille.it

$root(3)(8)-2root(3)(2/(27))+5root(6)(4)-7root(3)(2)=$

esercizio svolto o teoria

A cura di: Francesco Speciale

$root(3)(8)-2root(3)(2/(27))+5root(6)(4)-7root(3)(2)=$


$root(3)(8)-2root(3)(2/(27))+5root(6)(4)-7root(3)(2)=$
$root(3)(2^3)-2root(3)(2/(3^3))+5root(6)(2^2)-7root(3)(2)=$
semplificando
$2-2/3root(3)(2)+5root(3)(2)-7root(3)(2)=$
$(-2/3+5-7)root(3)(2)+2=((-2+15-21)/3)root(3)(2)+2=2-8/3root(3)(2)$.